2023
DOI: 10.15649/cuidarte.2451
|View full text |Cite
|
Sign up to set email alerts
|

Soledad, ansiedad y depresión en la adopción del rol de cuidador familiar del paciente crónico

Abstract: Introducción: En dirección a la teoría de Meleis, durante la transición como cuidador familiar, subyacen condiciones que facilitan o limitan la adopción del rol, y pueden afectar la integridad de esta persona. Objetivo: Determinar la relación entre la depresión, ansiedad y soledad con la adopción del rol de cuidadores familiares de personas con enfermedad crónica en Los Patios – Colombia durante el 2021. Materiales: Investigación cuantitativa analítica transversal que incluyó 120 pacientes y 120 cuidadores. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this sense, Parada et al (45) found that loneliness, depression, and anxiety (p<0.05) lead to a reduction in adoption of the caregiver role. Therefore, it is necessary to develop interventions targeted at improving the transition in a healthy way among these caregivers of OAs with post-stroke sequelae (50).…”
Section: Step A) Context and Populationmentioning
confidence: 98%
See 2 more Smart Citations
“…In this sense, Parada et al (45) found that loneliness, depression, and anxiety (p<0.05) lead to a reduction in adoption of the caregiver role. Therefore, it is necessary to develop interventions targeted at improving the transition in a healthy way among these caregivers of OAs with post-stroke sequelae (50).…”
Section: Step A) Context and Populationmentioning
confidence: 98%
“…It is important to note that the transition to the FC role can be emotionally and physically exhausting. Caregivers can experience care burden (34,38), fair health status perception (40,44), stress, anxiety, loneliness and depression (34,38,45), insomnia (32,46) or uncertainty and even fear of delegating care due to the radical change they are undergoing (47).…”
Section: Step A) Context and Populationmentioning
confidence: 99%
See 1 more Smart Citation